The association between social frailty, psychological resilience, and subsequent cognitive outcomes in older adults: A prospective cohort study - Yun-Jing Zhang; Cong Zhang; Qi-Yuan Lyu (The Journal of Nutrition, Health and Aging, 2025)
Background: The associations among social frailty, psychological resilience, and cognitive function, as well as their variations across sex and age, remain to be explored. The objective of the present study was to investigate these complex relationships in older adults. Methods: This study included 5555 participants from the CLHLS and categorized them into socially robust (n = 2229; 40.12%), social pre-frailty (n = 2624; 47.24%), and social frailty (n = 702; 12.64%) groups. The relationship between social frailty and cognitive outcomes was analyzed using logistic regression models and restricted cubic splines. The combined effects of social frailty and psychological resilience on cognitive outcomes were also analyzed. The mediating role of psychological resilience was evaluated using the SPSS PROCESS macro program. Results: Social pre-frailty (odds ratio [OR]: 1.81, 95%CI: 1.48–2.21) and social frailty (OR: 2.40, 95%CI: 1.87–3.09) were positively associated with cognitive impairment. Furthermore, social pre-frailty (OR: 1.71, 95%CI: 1.47–2.00), and social frailty (OR: 2.10, 95%CI: 1.69–2.60) were also positively associated with greater cognitive decline. Adverse cognitive outcomes demonstrated a nonlinear relationship with social frailty. Compared to individuals with social robustness and high psychological resilience, those with social frailty and low psychological resilience demonstrated higher odds ratios of developing cognitive impairment (OR: 3.65, 95%CI: 2.61–5.10) and experiencing greater cognitive decline (OR: 3.05; 95%CI: 2.33–4.00). The relationship between social frailty and negative cognitive outcomes was more pronounced among women and individuals younger than 80 years and exhibited a nonlinear pattern. Psychological resilience mediated the relationship between social frailty and cognitive outcomes in men (β = −0.0091, P < 0.05) and individuals with advanced age (β = −0.0087, P < 0.05). Conclusions: Social frailty is an independent influencing factor of adverse cognitive outcomes. Psychological resilience mediates the relationship between social frailty and cognitive function in men and subjects of advanced age.